Determinants and Constraints for Adoption of Zero Budget Natural Farming (ZBNF) Practices in Farmer Field School - Kumar, Sunil; Manjeet Singh Nain; V. Sangeetha; Satyapriya (Indian Journal of Extension Education, 2023)
Zero Budget Natural Farming (ZBNF) follows agroecological principles and promotes chemical-free farming. It has emerged as cost-effective farming improving soil fertility and providing chemical-free food. For determining factors for the adoption of ZBNF practices in the purposively selected Wardha district of Maharashtra, conducted during 2022-23, Logit regression and for analyzing the constraints, factor analysis was used. The study revealed significant factors like integrated soil fertility management practices, adoption of ZBNF practices, and IPM practices. The scarce raw materials for input preparation, weeds management and pests were identified as input related whereas, lack of knowledge about liquid fertilizers, insect/pest, and weed management practices were technology constraints, In case of labour and machinery constraints; non-availability of the bullock, high demand of skilled labour and high labour wages were reported. In case of institutional constraints, higher conversion period, high demand of skilled labour, and high certification fee were found. The assurance of better prices, purchase agencies at distant places, and lack of proper market structure were reported as the marketing constraints. In the case of political and legal constraints, a lesser number of FPOs, the synergy of the ZBNF practices , lack of globalized market, and the need for convergence were significant.